A copper-catalyzed oxidative coupling reaction of arylboronic acids, amines and carbon dioxide using molecular oxygen as the oxidant1. Issue 7 (28th February 2017) - Xiong, Wenfang; Qi, Chaorong; Guo, Tianzuo; Zhang, Min; Chen, Kai; Jiang, Huanfeng
Abstract : A Cu-catalyzed oxidative coupling reaction of arylboronic acids, amines and carbon dioxide is described, providing a route to O -aryl carbamates. Abstract : A Cu-catalyzed oxidative coupling reaction of arylboronic acids, amines and carbon dioxide is described for the first time in this paper. The reaction tolerates a wide range of functional groups, providing a convenient protocol for the synthesis of various O -aryl carbamates. The successful development of the transformation was enabled by the use of BF3 ·OEt2 as the promoter and molecular oxygen as the oxidant. Mechanistic studies suggested that the Cu II carbamato complex is involved in the catalytic transformation.